THE MISSING SOFT LINK? EVIDENCE FOR MARGINAL FAULT INTERACTION AT THE SOUTHERN MARGIN OF GERANEIA MOUNTAINS, CENTRAL GREECE - Kranis, H. (Bulletin of the Geological Society of Greece, 2016)
We examine the structure of the southern faulted margin of Geraneia Mountains, controlled by two marginal faults, namely the Loutraki and Kakia Skala Faults, which have been active in the Quaternary; however, Holocene activity on these structures has not been verified. Structural observations at the probable overlap zone between these two faults, suggest that they became soft-linked, or linkage ended at its early stage, before activity migrated basinwards, with consequent footwall backtilt. The affinity of the kinematics in the accommodation zone with the present-day extensional stress field might hint at possible Late Quaternary activity on these two major faults.